ARM BASED ON LEG BLOOD PRESSURES (ABLE-BP): CAN LEG BLOOD PRESSURE MEASUREMENTS PREDICT BRACHIAL BLOOD PRESSURE? INDIVIDUAL PARTICIPANT DATA META-ANALYSIS FROM THE INTERPRESS-IPD. (April 2021) - Mcdonagh, Sinead; Sheppard, James; Warren, Fiona; Boddy, Kate; Fordham, Jayne; Farmer, Leon; Lewis, Philip; Baumber, Rachel; Martin, Una; Clark, Christopher
Abstract : Objective: Hypertension, a key modifiable risk factor for prevention of stroke, is diagnosed and managed using upper arm blood pressure (BP) measurement. Amputations, altered muscle tone or limb deformities can prevent accurate brachial BP measurement and cardiovascular risk estimation, thus placing a cohort with known vascular risks at a disadvantage. Leg BP measurement is often used as a practical alternative, but limited data exist to guide clinicians' interpretation of leg BP values for the diagnosis and treatment of hypertension. Using data from the INTERPRESS-IPD Collaboration, which holds 34, 543 individual records from 15 international studies, we will examine the relationship between arm and leg BP, develop and validate a multivariable model predicting arm BP from leg BP and investigate the prognostic role of leg BP in cardiovascular event and mortality risk prediction. Design and method: In an observational cohort design, individual participant data meta-analyses will be undertaken to explore cross-sectional relationships between arm and leg BP in multivariable models. Using hierarchical linear regression models, we will investigate the association between arm and leg BP and participant characteristics. Planned predictor variables will include age, sex, cardiovascular disease risk and past medical history. Prognostic models will be derived for all-cause and cardiovascular mortality and cardiovascular events. Heterogeneity will be assessed using I 2 2 and tau 2 . Study quality will be assessed using a modified Quality In Prognostic Studies tool. Results: Arm and leg BP records exist for 34, 543 individuals. The median follow-up period is 8.5 years, with 3, 870 participants experiencing cardiovascular events and 3, 096 dying within 10 years. Further analyses are underway and arm-leg BP models will be presented at the conference. Figure. No caption available. Conclusions: We will provide the first evidence-based method for estimating individual brachial systolic BP, and cardiovascular risk, from leg BP measurements. Our findings will support clinicians and patients in detecting and managing hypertension more effectively where leg measurements are required.